Mapping and assessment of ecosystems and their services : an EU wide ecosystem assessment in support of the EU biodiversity strategy. - Maes, Joachim; Teller, Anne; Erhard, Markus; Condé, Sophie; Vallecillo, Sara; Barredo, José Ignacio; Paracchini, Maria Luisa; Abdul Malak, Dania; Trombetti, Marco; Vigiak, Olga; Zulian, Grazia; Addamo, Anna Maria; et al. (Publications Office of the European Union, 2020)
Europe’s ecosystems, on which we depend for food, timber, clean air, clean water, climate regulation and recreation, suffer from unrelenting pressures caused by intensive land or sea use, climate change, pollution, overexploitation and invasive alien species. Ensuring that ecosystems achieve or maintain a healthy state or a good condition is thus a key requirement to secure the sustainability of human activities and human well-being. This guiding principle applies for all ecosystems including marine and freshwater ecosystems, natural and semi-natural areas such as wetlands or heathlands but also managed ecosystems such as forests, farmlands and urban green spaces. Knowledge about ecosystem condition, the factors that improve or decline that condition, and the impacts on ecosystem services, with the benefits they deliver to people, is key to effective management, decision-making and policy design. Such an understanding helps target actions for conservation or restoration and more broadly sustainable use. The Biodiversity Strategy to 2020 includes the development of an integrated framework to monitor whether the actions undertaken are delivering on the ground. This assessment presents the changes in pressures and ecosystem condition in the EU and its marine regions using the year 2010 as a policy baseline. The following ecosystems are analysed: urban ecosystems, agroecosystems (croplands and grasslands), forests, wetlands, heathlands and shrub, sparsely vegetated lands, rivers and lakes, and marine ecosystems. The assessment is based on the best available European data. In addition, this report contains crosscutting assessments on climate change, invasive alien species, landscape mosaic, soil and ecosystem services.
Este informe constituye la evaluación integral a escala europea del estado de los ecosistemas y de los servicios que proporcionan, en el marco de la iniciativa MAES (Mapping and Assessment of Ecosystems and their Services) de la Comisión Europea y la Agencia Europea de Medio Ambiente. Su objetivo es establecer una base de conocimiento homogénea, comparativa y reproducible que permita evaluar el estado de los ecosistemas europeos, apoyar el diseño e implementación de políticas ambientales comunitarias y contribuir al cumplimiento de los compromisos internacionales en materia de biodiversidad. El documento desarrolla metodologías armonizadas para la cartografía, evaluación y seguimiento de ecosistemas terrestres y acuáticos, integrando indicadores estructurales, funcionales y de presión. Incluye propuestas de indicadores operativos y marcos conceptuales que permiten valorar la salud de los ecosistemas, cuantificar los servicios que proporcionan y analizar los cambios derivados de presiones antrópicas y ambientales. La información se estructura por tipos de ecosistemas —bosques, agroecosistemas, humedales, ríos y lagos, entre otros—, desarrollando metodologías específicas para cada uno de ellos. El enfoque adoptado se basa en datos abiertos y armonizados provenientes de iniciativas europeas como Copernicus, EIONET, LUCAS o EEA, lo que garantiza su reproducibilidad y aplicación homogénea. La metodología propuesta permite identificar tendencias, evaluar el estado de conservación, detectar áreas críticas y apoyar decisiones de gestión territorial y conservación.
Keywords: Biodiversidad; Ecosistemas - Gestión; Unión Europea - Política ambiental; Europe; Biodiversity Strategy to 2020; Ecosystem assessment